Active stiffening for soft multi-rotor drones - Peh, Yu Yun (Nanyang Technological University, 2023)
In the emerging field of soft robotics, nature has inspired many engineering innovations that incorporate flexible elements to improve the efficiency and robustness of flight in traditionally rigid drones. However, soft structures pose challenges to the controllability of the drone’s flight due to their flexibility and easily deformable nature. Hence, this project aims to incorporate the best of both worlds by implementing an active stiffening system that allows a soft drone to fly agilely, while being able to morph its shape and conform to its environment. A stiffening system was implemented on a circular drone, which achieved stiffening of up to 257% under static conditions.